An organic–inorganic hybrid perovskite logic gate for better computing. Issue 41 (23rd September 2015) - Lin, Guoming; Lin, Yuanwei; Cui, Rongli; Huang, Huan; Guo, Xihong; Li, Cheng; Dong, Jinquan; Guo, Xuefeng; Sun, Baoyun
Abstract : An electrically bistable and non-volatile rewritable memory effect on a sandwich architecture, ITO/PEDOT:PSS/organic–inorganic hybrid perovskite/Cu, is shown. Abstract : A practicable means of significantly reducing the energy consumption and speeding up the operating rate of computer chips is to place the processor and memory into one device, which processes and stores information simultaneously like the human brain. Here we demonstrate a novel sandwich architecture where organic–inorganic hybrid perovskite materials could be used as building-block materials for non-volatile memristors, accompanied with photoresponsive performance. Owing to the distinct photo-response of the two resistance states of the memristor, it is feasible to utilize the device as a logic OR gate by employing an electrical field and light illumination as input sources. This study provides potential applications in logic circuits, optical digital computation and optical quantum information for beneficial supplementation of the von Neumann architecture, or even for computing beyond it.